Video Tutorials on Education Statistics Course Assisted with Screencastify: Validity and Feasibility - Wahyuni, Molli; Hidayat, Adityawarman; Zulhendri, Zulhendri; Gistituati, Nurhizrah (Universitas Pendidikan Ganesha, 2021)
The students' difficulty understanding lecture material is due to the lack of learning media that can help students learn independently. This study aims to develop a learning video tutorial based on the Screencastify screen record. This type of research is developmental research. The development model used is the Plomp development model. The development of the learning model is divided into three stages, namely the initial research, the prototype production, and the model assessment stage. The technique of collecting data in this research is observation and interview. The instrument used to collect data was a questionnaire. Data analysis was carried out to know the feasibility or validity of the product being developed. Media testing uses expert judgment. The validity measurement uses the Likert scale. The results of the validity and practicality of the validators were carried out by using the Intraclass Correlation Coefficient (ICC) test using the SPSS program. The results showed that the educational statistics tutorial videos were classified as valid for all categories and very practical, with a score of 85.5 based on students' answers as respondents. It can be concluded that the learning video developed is valid so that it is feasible to be applied in the learning process.